Was it a clutch performance? A qualitative exploration of the definitional boundaries of clutch performance. (September 2022) - Schweickle, Matthew J.; Vella, Stewart A.; Swann, Christian
Abstract: Objectives: Clutch performance refers to positive performance under pressure. Definitions of clutch performance, however, differ on the performance level required to constitute this phenomenon. This definitional divergence centres on whether clutch performance requires increased, or maintained, performance. Further, it is unclear what performance benchmark (e.g., season average) clutch performances should be compared against. Accordingly, this study aimed to explore athletes' perceptions of what performance level is required for clutch performance, and what performance benchmarks clutch performances are compared against. Method: Twenty-four athletes ( M age = 27.13 years) participated in event-focused, semi-structured interviews soon after a positive performance under pressure ( M = 93 h later). Data were analysed utilising reflexive thematic analysis. Results: Three themes were generated: (1) clutch performance is assessed against goal achievement, suggesting that the achievement of self-referenced goals is the primary indicator athletes' use to assess clutch performance; (2) clutch performance exists on a performance spectrum, suggesting that the performance level required for clutch performance differs due to the appraisal of pressure and the athletes' own goals; and (3) different benchmarks are used to assess clutch performance, suggesting that athletes' may draw on both previous performances, and the performance itself, to assess clutch performance. Conclusions: This study suggested that clutch performance is a situational and context-dependent phenomenon. Specifically, athletes assessed clutch performance on the extent to which they perceived achievement of self-referenced goals. Defining clutch performance in this manner may resolve tensions between existing definitions, and further, may facilitate development of a measure of clutch performance. Highlights: Twenty-four athletes were interviewed within four days of performing under pressure. Athletes use self-referenced goal achievement to assess clutch performance. Clutch performance may be situational and context-dependent. A refined definition of clutch performance is provided.